تلقي رواية: (اللاز)للطاهر وطار في الخطاب النقدي المُعاصر -قراءة وصفيّة تـحليليّة لنماذج مختارة - بوفلاقة, محمد سيف الاسلام (جامعة الوادي - University of Eloued, 2021)
يجمع الدارسون-أو يكادون-، على أن مرحلة السبعينيات،تعد المرحلة الفعلية التي عرفت قفزة حقيقية للنهوض الروائي الفني في الجزائر؛حيث إنها مرحلة تأصيل الرواية الجزائرية؛ والتي ظهرت فيها مجموعة من الأعمال نذكر منها:«ريح الجنوب» لعبد الحميد بن هدوقة، و«اللاز»للطاهر وطار؛ موضوع بحثنا، وقد وصفت هذه الرواية بأنها التجربة الروائية الجديدة المتقدمة في الفترة التي أعقبت الاستقلال، حيث مكنت الجزائريين من الانفتاح الحر على عوالم الرواية العربية المعاصرة، ومما لا يشوبه ريب أن الكتابة الروائية خلال تلك الفترة سجلت شجاعة في طروحاتها الفكرية،ومغامراتها الفنية؛ لأن الكاتب أضحى ينطلق من رؤى تعبيرية متحررة لا يردعها الواقع السياسي الاستعماري ؛ مما مكنها من نقل روح الشعب الجزائري، والتوغل في شتى فضاءاته الاجتماعية. و نروم من خلال هذا البحث تسليط الضوء على هذه الرواية المتميزة، والتي توصف بالرواية المفصلية؛ كونها فصلت بين مرحلة التأسيس، ومرحلة التأصيل للرواية العربية في الجزائر،كما نسعى إلى الوقوف مع بعض الرؤى النقدية التي قدمت ،وهي بصدد مدارسة رواية«اللاز»؛ التي لها أهمية استثنائية في تاريخ الأدب الجزائري. Scholars agree - or almost - that the seventies is the actual stage that witnessed a real leap for the artistic novel's advancement in Algeria, as it is the stage of rooting the Algerian novel; And in which a group of works appeared in it, including: “The Wind of the South” by Abd al-Hamid bin Hadouka, and “Laz” by al-Taher and flew The subject of our research, and this novel has been described as the new advanced fictional experience in the post-independence period, as it enabled Algerians to open up freely to the worlds of contemporary Arab novels, and it is undeniable that fictional writing during that period recorded courage in its intellectual propositions and artistic adventures; Because the writer now starts from expressive visions that are not deterred by the colonial political reality. This enabled it to transmit the spirit of the Algerian people and penetrate its various social spaces. Through this research, we aim to shed light on this distinguished narrative, which is described as an articulated narrative; As it separated the foundation stage from the rooting stage of the Arabic novel in Algeria, we also seek to stand with some of the critical visions that were presented, which are in the process of studying the novel "Laz"; Which has an exceptional importance in the history of Algerian literature. Key words: receive; a novel ; Speech ; Forms; reading.
مقال
Keywords: تلقي ؛ رواية ؛ خطاب ؛ نماذج؛ قراءة.; receive; a novel ; Speech ; Forms; reading